2018
DOI: 10.1038/s41598-018-32588-8
|View full text |Cite
|
Sign up to set email alerts
|

Skin α-synuclein deposits differ in clinical variants of synucleinopathy: an in vivo study

Abstract: We aimed to characterize in vivo α-synuclein (α-syn) aggregates in skin nerves to ascertain: 1) the optimal marker to identify them; 2) possible differences between synucleinopathies that may justify the clinical variability. We studied multiple skin nerve α-syn deposits in 44 patients with synucleinopathy: 15 idiopathic Parkinson’s disease (IPD), 12 dementia with Lewy Bodies (DLB), 5 pure autonomic failure (PAF) and 12 multiple system atrophy (MSA). Ten healthy subjects were used as controls. Antibodies again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
98
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 44 publications
8
98
1
1
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24] This observed high diagnostic accuracy of skin biopsy examination using anti-pSyn antibody may be because the majority of the studies used thick cryosections from multiple sampling sites with the double immunofluorescence technique to investigate abnormal α-syn deposits in cutaneous autonomic fibers. Some researchers reported that sensitivity varies depending on the location of the sampling site with the posterior region of the neck showing the best sensitivity, 22,25,31 and examining multiple sampling sites would obviously improve sensitivity, as was shown by our subgroup analysis. Thick cryosections examined with double immunofluorescence technique enable evaluation of larger areas and tracing of the nerve compared to thin paraffin sections, which would make distinction of abnormal α-syn deposits in neurites from nonspecific immunostaining easier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19][20][21][22][23][24] This observed high diagnostic accuracy of skin biopsy examination using anti-pSyn antibody may be because the majority of the studies used thick cryosections from multiple sampling sites with the double immunofluorescence technique to investigate abnormal α-syn deposits in cutaneous autonomic fibers. Some researchers reported that sensitivity varies depending on the location of the sampling site with the posterior region of the neck showing the best sensitivity, 22,25,31 and examining multiple sampling sites would obviously improve sensitivity, as was shown by our subgroup analysis. Thick cryosections examined with double immunofluorescence technique enable evaluation of larger areas and tracing of the nerve compared to thin paraffin sections, which would make distinction of abnormal α-syn deposits in neurites from nonspecific immunostaining easier.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating PD from other diseases that can also display abnormal α-syn deposits and identification of prodromal PD are important topics. Other Lewy body disorders, such as DLB and PAF, as well as RBD, which is often considered as prodromal PD, can exhibit α-syn immunoreactivity in a pattern similar to that of PD, 14,22,24,25,43 whereas MSA can exhibit α-syn immunoreactivity in a pattern different from that observed in PD. For example, studies using skin biopsy have suggested that MSA presents with selective somatosensory fiber involvement, which is in contrast to the selective involvement of autonomic fibers in PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), human skin biopsy of patients with idiopathic PD (Donadio et al . ), and in human post‐mortem brain tissues from PD, DLB, AD, and control cases (Vaikath et al . )…”
Section: α‐Syn Specific Antibodies: Invaluable Tools For Synucleinopamentioning
confidence: 99%
“…2). Furthermore, the conformational specificity of these antibodies have been utilized to detect a-syn aggregates in biochemical studies (Leung et al 2015), in neurons of Caenorhabditis elegans (Kim et al 2016) and rats (Duffy et al 2018), guinea-pig ileum (Sharrad et al 2017), human skin biopsy of patients with idiopathic PD (Donadio et al 2018), and in human post-mortem brain tissues from PD, DLB, AD, and control cases (Vaikath et al 2018)…”
Section: A-syn Specific Antibodies: Invaluable Tools For Synucleinopamentioning
confidence: 99%